Penanaman Mangrove di Desa Pulo Panjang Kabupaten Serang Dalam Bakti PLN Indonesia Power Cilegon PGU di Bidang Lingkungan - Shofa Alya Cantika; Dadan Darmawan (Arsil Media, 2023)
Indonesia is an archipelagic country because it has many islands spread throughout Indonesia, one of which is Pulo Panjang, which is an island located in Banten Bay in the Puloampel District area of Serang Regency with an area of around 8.2 km² and a population of 39,927 people in 2021. Pulo Panjang has a village population called Pulo Panjang Village. This village is in a coastal area, so as is known, coastal areas are vulnerable to natural disasters such as abrasion or erosion caused by beach wave activity. so there needs to be good management regarding coastal areas as in Law Number 27 of 2007. One of the efforts carried out by PT. PLN Indonesia Power Cilegon PGU as a company whose operational area is close to Pulo Panjang Village is planting mangroves on the beach to help prevent erosion or abrasion disasters and other natural disasters that may occur in Pulo Panjang Village